Effect of Feeding Interval on Finishing Performance of Beef Steers - Chance Fiehler; John Jaeger; Justin Waggoner; Keith Harmoney; K.C. Olson (Kansas Agricultural Experiment Station Research Reports, 2022)
It has long been accepted that optimal performance in beef cattle occurs when cattle are fed at a similar time each day. In fact, in Frederick Mumford’sSyllabus of Illustrated Lecture on Profitable Cattle Feedingpublished by the U.S. Department of Agriculture in 1905, Mr. Mumford stated, “Cattle should be fed at certain hours and in the same way. This cannot be varied 15 minutes without some detriment to the cattle.” Little research has been conducted examining interval of feed delivery. Most feedlot research examining feed delivery has focused on the comparison of once or twice daily feed delivery on animal performance. The current research examined beef steer finishing performance with stable or variable once daily feed delivery.
Keywords: body weight gain; feedlot; marbling score; variable diet delivery